2014
DOI: 10.1371/journal.pone.0094560
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as Assessed by Body Adiposity Index and Multivariable Cardiovascular Disease Risk

Abstract: To assess the role of body adiposity index (BAI) in predicting cardiovascular disease (CVD) and coronary heart disease (CHD) mortality, in comparison with body mass index (BMI), waist circumference (WC), and the waist circumference to hip circumference ratio (WHR). This study was a prospective 15 year mortality follow-up of 4175 Australian males, free of heart disease, diabetes and stroke. The Framingham Risk Scores (FRS) for CHD and CVD death were calculated at baseline for all subjects. Multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 30 publications
0
19
0
3
Order By: Relevance
“…BAI's ability to predict body fat has been analyzed in the literature, especially in relation to BMI. Some studies have shown that BAI is a better predictor of body fat when compared with BMI (Chang, Simonsick, Ferrucci, & Cooper, ; Dhaliwal, Welborn, Goh, & Howat, ; Godoy‐Matos et al, ; Johnson, Chumlea, Czerwinski, & Demerath, ; Silva et al, ; Sun et al, ;), while others have found a similar or higher capacity of BMI as a predictor of body fat when compared with BAI (Appelhans et al, ; Barreira et al, ; Freedman et al, ; Gibson, Atalayer, Flancbaum, & Geliebter, ; Lopez et al, ; Schulze & Stefan, ; Vinknes et al, ). In the present study, despite the strong correlation with DXA in men ( r = 0.72) and in women ( r = 0.78), BAI was not shown to be a better indicator of body fat than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…BAI's ability to predict body fat has been analyzed in the literature, especially in relation to BMI. Some studies have shown that BAI is a better predictor of body fat when compared with BMI (Chang, Simonsick, Ferrucci, & Cooper, ; Dhaliwal, Welborn, Goh, & Howat, ; Godoy‐Matos et al, ; Johnson, Chumlea, Czerwinski, & Demerath, ; Silva et al, ; Sun et al, ;), while others have found a similar or higher capacity of BMI as a predictor of body fat when compared with BAI (Appelhans et al, ; Barreira et al, ; Freedman et al, ; Gibson, Atalayer, Flancbaum, & Geliebter, ; Lopez et al, ; Schulze & Stefan, ; Vinknes et al, ). In the present study, despite the strong correlation with DXA in men ( r = 0.72) and in women ( r = 0.78), BAI was not shown to be a better indicator of body fat than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…En población con ECV, Dhaliwal et al 36 describen también correlaciones entre el IAC y el IMC, la CC y el PC (p < 0,001). Sin embargo, tras ajustar por edad la CC y la relación cintura-cadera se asociaron significativamente como predictores de ECV con OR 3,84 (IC 95%: 1,59-9,25) y OR 5,42 (IC 95%: 2,12 a 13,89), respectivamente.…”
Section: Discussionunclassified
“…15 More recently, BAI was shown to lack predictive ability for CVD mortality after age and risk factor adjustments in Australian men. 16 Among Asians, BAI was described to be an inappropriate biomarker for screening hypertension, dyslipidemia, metabolic syndrome and carotid intimamedia thickening in the Chinese population compared with WC and BMI. 22 Our study also showed that BAI is an ineffective determinant of body fatness for Asians.…”
Section: Discussionmentioning
confidence: 99%